The morphological features of above-ground parts of Juniperus sabina in Central Kazakhstan - Abdikarimova, P.U.; Kali, A.K.; Ishmuratova, M.Yu.; Ramazanov, A.K.; Nurkenova, A.T. (Fundamental and Experimental Biology, 2024)
In the article the results of the study of morphological parameters of vegetative organs of Juniperus sabina growing in the vicinity of Karaganda city, Karkaraly and Ulytau Mountains, hills of Zhanaarka district were presented. The results of research are based on complexly conducted field and experimental materials, scientifically substantiated methods and modern statistical analyses evaluating the reliability criterion. It is noted that for the leaf length indicator the maximum values were for individuals from Zhanaarka district, the minimum values were for the vicinity of Karaganda city. For leaf width and annual growth value, no reliable difference was observed between individuals from different growing points. The maximum size of plants was observed in the vicinity of Karaganda city, the minimum size was observed for individuals from Zhanaarka and Ulytau districts. The obtained data are conditioned by different degree of environmental pollution and climatic conditions.